No Polarity-specific Modulation of Prefrontal-to-M1 Interhemispheric Inhibition by Transcranial Direct Current Stimulation Over the Lateral Prefrontal Cortex. (1st March 2023) - Uehara, Shintaro; Mawase, Firas; Cherry-Allen, Kendra M.; Runnalls, Keith; Khan, Maheen; Celnik, Pablo
Highlights: Neurophysiological evidence of prefrontal non-invasive stimulation remains unclear. Aftereffect of prefrontal transcranial direct current stimulation was investigated. Presence of aftereffect was assessed by dual-site transcranial magnetic stimulation. A biomarker of prefrontal excitability failed to show substantial aftereffect. Transcranial current may have too-small effects to be detected by the present proxy. Abstract: The lateral prefrontal cortex (PFC) plays a variety of crucial roles in higher-order cognitive functions. Previous works have attempted to modulate lateral PFC function by applying non-invasive transcranial direct current stimulation (tDCS) and demonstrated positive effects on performance of tasks involving cognitive processes. The neurophysiological underpinning of the stimulation effects, however, remain poorly understood. Here, we explored the neurophysiological after-effects of tDCS over the lateral PFC by assessing changes in the magnitude of interhemispheric inhibition from the lateral PFC to the contralateral primary motor cortex (PFC-M1 IHI). Using a dual-site transcranial magnetic stimulation paradigm, we assessed PFC-M1 IHI before and after the application of tDCS over the right lateral PFC. We conducted a double-blinded, crossover, and counterbalanced design where 15 healthy volunteers participated in three sessions during which they received either anodal, cathodal, and sham tDCS. In order to determine whether PFC-M1 IHI could be modulated at all, we completed the same assessment on a separate group of 15 participants as they performed visuo-motor reaction tasks that likely engage the lateral PFC. The results showed that tDCS over the right lateral PFC did not modulate the magnitude of PFC-M1 IHI, whereas connectivity changed when Go/NoGo decisions were implemented in reactions during the motor tasks. Although PFC-M1 IHI is sensitive enough to be modulated by behavioral manipulations, tDCS over the lateral PFC does not have substantial modulatory effects on PFC to M1 functional connectivity, or at least not to the degree that can be detected with this measure.